The Archival Turn as Practice - Cvetkovich, Ann (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
This article reflects on the significance of the affective turn for work in cultural studies and queer studies, paying particular attention to the distinction between archival theory and archival practice. It focuses on queer archives and especially the creative methods of artists in the archives. It closes with a brief return to Derrida’s Archive Fever by way of acknowledging its influence.